UPAYA MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN ASLI 1-5 MELALUI PERMAINAN KERETA ANGKA PADA ANAK TUNAGRAHITA SEDANG - Reni - Andriani (Universitas Negeri Padang, 2012)
This research of background overshadow by problems which is researcher find in SLB Country Five clan of Batusangkar, a child of tunagrahita which is not yet recognized number. From result of perception of the child have spelled out members, but asked which/such number 1 until five child cannot answer him. this research aim to to increase ability recognize number specially original number 1until 5 by using game of number cart.Research type the used is Single Subject Research ( SSR) with A-B desain. Analysis Data show length of is condition of baseline is 10 times perception, during 10 day, while condition of intervention is 11 times perception, during 11 day. At condition of baseline on first until sixth day of child get 0%, and on seventh until day the tenth child get 20 . while at condition of intervention on eleventh until child compassion day get percentage 40%, fourteenth day until child compassion day get 60%, compassion day and eighteenth day of child get 80% and on compassion until day of keduapuluhstu got by percentage is child 100%. Thereby raised hypothesis previously can be accepted, its meaning through game of number cart can improve ability recognize original number 1-5 at child of tunagrahita is. From result of this research is expected can be of benefit to researcher and teacher here in after.